2018
DOI: 10.1186/s12893-018-0339-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous therapy of a mediastinal lymphangioma with fibrin glue: case report with clinical success after 4 years

Abstract: BackgroundLymphangioma of the mediastinum is a rare benign tumor, and most of the cases are treated by a surgical approach.Case presentationThis work reports the case of a 62-year-old female with a large lymphangioma extending from her neck to her abdomen with dysphagia, dyspnea, and cough for 2 months. Because of the location of the mass, only bilateral excision could remove the multiloculated cyst completely. However, the patient’s overall physical condition was very poor, and we thought she could not tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Less than 1 percent of ectopic thyroid tissue is reported in the mediastinum [6] . In cases of mediastinal ectopic thyroid, the orthotropic thyroid usually coexists and patients are euthyroid.…”
Section: Introductionmentioning
confidence: 99%
“…Less than 1 percent of ectopic thyroid tissue is reported in the mediastinum [6] . In cases of mediastinal ectopic thyroid, the orthotropic thyroid usually coexists and patients are euthyroid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there have been reports that fibrin sealants can precipitate acute immune responses; chronically, they are associated with adhesion formation and infection [ 9 ]. In addition, the fibrin sealants can be used as an adhesive material for another type of operations [ 10 ]. The polyethylene glycol-based hydrogel sealant; as DuraSeal (Covidien); which is biocompatible, self-polymerizing, nontoxic, water-soluble, absorbable, flexible, and strongly adherent to tissue has been recently used to avoid CSF leak complications; and there has been no reported sealant-related adverse events in the literature [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…bleomycin, doxycycline, polidocanol, zein solution, OK-432 or fibrin glue) are successfully used in sclerotherapy of lymphangiomas which can be additionally given during surgery or percutaneous drainage. These substances can be also applied as primary treatment alone [4,12,13]. Single cases of successful treatment of lymphangiomas using oral drugs, such as propranolol [14] and sirolimus [15], were reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may occur in any part of the gastrointestinal tract and may be detected in the retroperitoneal space, spleen, liver, gall bladder, adrenal glands, pancreas and the lesser omentum. Studies also reported simultaneous occurrence of lymphangioma in the abdominal cavity and mediastinum [4]. Clinical presentation can be asymptomatic, chronic with non-specific symptoms associated with the mass effect (lumbar pain, vomiting, bowel movement disorder) or acute symptoms related to intestinal obstruction [3], infection of the cystic mass, or bleeding from/ into the tumor [5].…”
Section: Introductionmentioning
confidence: 99%